An investigation of psycho-social factors associated with the uptake of pre-pregnancy care in Australian women with type 1 and type 2 diabetes. (June 2013) - Komiti, A.; Jackson, H. J.; Nankervis, A.; Conn, J.; Allan, C.; Judd, F.
Abstract Pre-pregnancy care (PPC) reduces adverse pregnancy outcomes for women with pre-existing diabetes. Yet, despite the compelling case for PPC, participation rates remain poor. The reasons for poor participation are as yet unclear. The aim of this study was to further our understanding of the factors-associated PPC uptake, particularly attitudes and beliefs towards PPC using models of health behaviour: The Health Belief Model, Social Cognitive Theory, and Theory of Reasoned Action. Participants comprised 123 women with type 1 and 2 diabetes attending outpatient clinics for diabetes and pregnancy, who completed questionnaires. Logistic regression analysis indicated that after adjusting for socio-demographic factors, exposure to a greater number of cues was a significant predictor of PPC participation (odds ratio [OR]: 1.93; 95% confidence interval [95% CI]: 1.13–3.28). Other significant predictors of PPC uptake were older age (OR: 1.13; 95% CI: 1.01–1.26) and not having children (OR: 3.93; 95% CI: 1.28–12.06). The findings from this study support initiatives to provide cues to PPC for women with diabetes to enhance PPC uptake. Further, some groups such as younger women as well as women with children may possibly be considered for the focus of more vigorous intervention efforts.